Bacterial Diversity and Biogeochemical Processes of Oil-Contaminated Groundwater, Baoding, North China. Issue 6 (2nd July 2016) - Sheng, Yizhi; Tian, Xiaowei; Wang, Guangcai; Hao, Chunbo; Liu, Fei
ABSTRACT: A total of 43 groundwater samples were collected from 9 multimonitoring wells at a petrochemical site, Baoding City, North China, from June 2008 to December 2009 to investigate the biogeochemical processes and/or bacterial conmmunity using both culture-dependent and -independent methods. The results showed that aromatic hydrocarbons and chlorinated hydrocarbons were the major pollutants in the groundwater. Denitrification and iron reduction might be the main biogeochemical processes in the aquifers at this site, which seemed to transform from denitrification-dominated to iron reduction-dominated in some sections. Denaturing gradient gel electrophoresis (DGGE) revealed that the dominant bacterial groups of the groundwater were related to some oil-degrading bacteria, which can grow under denitrifying, iron-reducing and sulfate-reducing anaerobic conditions. In some serious contaminated groundwater niches, there might be sulfur cycles, as sulfur oxidizer was also abundant, which was further confirmed by 16S rRNA gene cloning analysis. The operational taxonomic units (OTUs) that highly related to Pseudomonas sp., Hydrogenophaga sp., Sphingomonas sp., Ferribacterium sp. and Sulfuricurvum Kujiense etc. were predominant in the groundwater contaminated by chlorinated hydrocarbons (CHCs), benzene, toluene, ethylbenzene, and xylenes (BTEX) and/or polycyclic aromatic hydrocarbons (PAHs), respectively. Biodiversity seemed to be undermined by oil contamination, and varied with seasons. The bacterial community in the contaminated groundwater was largely determined by the groundwater geochemistry.